Uterine scar rupture at the site of the placenta accreta presenting as a case of sudden death - Swapnil Prabhakar Akhade; Pankaj Suresh Ghormade; Ajay Bhengra; Krishnadutt Chavali; Nighat Hussain (University of São Paulo, 2021)
Uterine rupture during pregnancy is a known complication of placenta accreta. This paper presents a case of sudden maternal death in the 27th week of gestation due to a ruptured uterine scar at the site of placenta accreta with a short inter-pregnancy period of 6 months with previous two C-sections. Autopsy findings revealed a massive hemoperitoneum and a thinned out anterolateral uterine wall. Internal examination revealed clotted and fluid blood in the peritoneal cavity with rupture of the anterior uterine wall at the site of the placenta accreta in a healed cesarean section scar. Placenta accreta is a rare complication of pregnancy. However, it is becoming more frequent and a significant risk factor with the increasing rate of C-section.